PENINGKATAN KETERAMPILAN SISWA TUNA RUNGU WICARA DALAM MENARI MENGGUNAKAN METODE ADD-ON (LINKED) - Anggraini, Dwi; Hasnawati, Hasnawati (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This training is motivated by competitive conditions to find increasingly tricky work, especially for children with special needs who, in this case, are deaf and speechless. For this reason, there is a need for skills training so that they can compete with healthy individuals, one of which is dance training for the creation of the Bengkulu area for deaf students of Dharma Wanita Persatuan Bengkulu Province. The method of activity is in the form of exercise conducted, starting with preparation and implementation. The results of the use showed that the elements of wired 14 students (87.5%) could dance with the correct forms of motion, and 13 students (81.25%) students could memorize the sequence of movements. The element of wirama 13 students (81.25%) students can move in harmony with accompaniment music. As for the aspect of wirasa, seven students (43, 75%) students can express themselves according to the theme of dance and confidence. However, this training can be said to be successful because students already have the dance skills created by Bengkulu, although there are still many shortcomings.